An Analytical Study on Users’ Profile of Micro Finance In Madhya Pradesh State - Mrs. Khushboo Kumari and Dr. N.K. Shrivastava (International journal of economic perspectives, 2018)
Micro finance is a financial service provided to un-employed or low income people or group of people who otherwise would have no other financial services. Microfinance allows people to take small scale loans on less interest safely, and in manner that is consistent with ethical lending process. Madhya Pradesh is in a phase of the Indian financial growth, which is anticipated to outpace the increase in the present world in the subsequent 10 years. Now Microfinance Institutions have been gaining reputation in the latest years and are now regarded as high-quality tools for assuaging poverty. This research study is a short attempt to analyze the profile of Microfinance users in Madhya Pradesh state. There are mainly 04 basic points to analyze the Microfinance users’ profile, i.e. Age, marital status, monthly income and gender etc. The existing lookup is a conceptual find out about of Microfinance Institutions in India as properly as in the nation of Madhya Pradesh. The data received from this study are quite interesting and have been depicted the complete scenario of the Microfinance users.